DARURAT DEMOKRASI: KRISIS KEADILAN DAN BIAS KEPENTINGAN - Willfridus Demetrius Siga; Onesius Otenieli Daeli (Sapientia Humana: Jurnal Sosial Humaniora, 2024)
Democracy emergencies often become a phenomenon and issue in Indonesia. Responses to this issue are certainly very diverse. There are biases and prejudices directed at the state of democracy in Indonesia. At the concrete and practical level, democracy itself is a tool to achieve common goals. However, on the other hand, democracy is in an emergency condition because it has been used as a non-transparent tool, and democracy is even used as a means to perpetuate the pursuit of interests. This research aims to provide new discourse and insights into the crisis situation and democratic bias that is occurring, while also trying to find answers regarding the political role of citizens in overcoming the crisis. The method used in the activities is the qualitative discourse method through literature study, observation, and focus group discussion. (FGD). The research results indicate that the issues of demos and krator need to be returned to their essence, both conceptually and in practice, in the political life of the nation and state. Individuals who are called to enter the world of politics and run a democracy need to be accompanied by knowledge and experience (arête). The practice of democracy becomes effective when those involved in political decision-making are able to perform their duties and produce policies that do not lead to the common good. If placed in the context of Indonesia, Pancasila should become a source and inspiration for democracy that prioritises common interests and justice.